Simultaneous Single Unit Recording in the Mitral Cell Layer of the Rat Olfactory Bulb under Nasal and Tracheal Breathing - MARÍA DE LA LUZ AYLWIN; EUGENIA DÍAZ; PEDRO E MALDONADO (Biological Research, 2005)
Odor perception depends on the odorant-evoked changes on Mitral/Tufted cell firing pattern within the olfactory bulb (OB). The OB exhibits a significant "ongoing" or spontaneous activity in the absence of sensory stimulation. We characterized this ongoing activity by simultaneously recording several single neurons in the mitral cell layer (MCL) of anesthetized rats and determined the extent of synchrony and oscillations under nasal and tracheal breathing. We recorded 115 neurons and found no significant differences in the mean firing rates between both breathing conditions. Surprisingly, nearly all single units exhibited a long refractory period averaging 14.4 ms during nasal respiration that was not different under tracheal breathing. We found a small incidence (2% of neurons) of gamma band oscillations and a low incidence (8.1%) of correlated firing between adjacent MCL cells. During nasal respiration, a significant oscillation at the respiratory rate was observed in 12% of cells that disappeared during tracheal breathing. Thus, in the absence of odorants, MCL cells exhibit a long refractory period, probably reflecting the intrinsic OB network properties. Furthermore, in the absence of sensory stimulation, MCL cell discharge does not oscillate in the gamma band and the respiratory cycle can modulate the firing of these cells